Ventilation heterogeneity in the acinar and conductive zones of the normal ageing lung. Issue 9 (27th April 2012) - Verbanck, Sylvia; Thompson, Bruce R; Schuermans, Daniel; Kalsi, Harpal; Biddiscombe, Martyn; Stuart-Andrews, Chris; Hanon, Shane; Van Muylem, Alain; Paiva, Manuel; Vincken, Walter; Usmani, Omar
Abstract : Rationale: Small airways function studies in lung disease have used three promising multiple breath washout (MBW) derived indices: indices of ventilation heterogeneity in the acinar (Sacin ) and conductive (Scond ) lung zones, and the lung clearance index (LCI). Since peripheral lung structure is known to change with age, ventilation heterogeneity is expected to be affected too. However, the age dependence of the MBW indices of ventilation heterogeneity in the normal lung is unknown. Objectives: The authors systematically investigated Sacin, Scond or LCI as a function of age, testing also the robustness of these relationships across two laboratories. Methods: MBW tests were performed by never-smokers (50% men) in the age range 25–65 years, with data gathered across two laboratories (n=120 and n=60). For comparison with the literature, the phase III slopes from classical single breath washout tests were also acquired in one group (n=120). Measurements and main results: All three MBW indices consistently increased with age, representing a steady worsening of ventilation heterogeneity in the age range 25–65. Age explained 7–16% of the variability in Sacin and Scond and 36% of the variability in LCI. There was a small but significant gender difference only for Sacin . Classical single breath washout phase III slopes also showed age dependencies, with gender effects depending on the normalisation method used. Conclusions: With respect to the clinical response, age is a small but consistent effect that needs to be factored in when using the MBW indices for the detection of small airways abnormality in disease.